Not Merely a Constraint: How the Constrained Lever Model Shapes Mandibular Evolution via Integration - Hyunwoo Jung; Karen L. Baab; David Strait; Campbell Rolian (Evolutionary Biology, 2026)

A phylogenetic perspective on the evolution of early hominin foot morphology - Yeganeh Sekhavati; Thomas Cody Prang; David Strait (Journal of Human Evolution, 2025)

Estimating ancestral ranges and biogeographical processes in early hominins - Yeganeh Sekhavati; David Strait (Journal of Human Evolution, 2024)

Functional morphological integration related to feeding biomechanics in the hominine skull - Hyunwoo Jung; David Strait; Campbell Rolian; Karen L. Baab (Journal of Human Evolution, 2023)

Reply to Rak et al. (2021) “The DNH 7 skull of Australopithecus robustus from Drimolen (Main Quarry), South Africa” [J. Hum. Evol. 151 (2021), 102913] - David S. Strait; Jesse M. Martin; A.B. Leece; Stephanie E. Baker; Andy I.R. Herries (Journal of Human Evolution, 2023)

An updated analysis of hominin phylogeny with an emphasis on re-evaluating the phylogenetic relationships of Australopithecus sediba - Carrie S. Mongle; David S. Strait; Frederick E. Grine (Journal of Human Evolution, 2023)

Discovery of cryptotephra at Middle–Upper Paleolithic sites Arma Veirana and Riparo Bombrini, Italy: a new link for broader geographic correlations - Jayde N. Hirniak; Eugene I. Smith; Racheal Johnsen; Minghua Ren; Jamie Hodgkins; Caley Orr; Fabio Negrino; Julien Riel‐Salvatore; Shelby Fitch; Christopher E. Miller; Andrea Zerboni; Guido S. Mariani; et al. (Journal of Quaternary Science, 2020)
Chemical characterization of cryptotephra is critical for temporally linking archaeological sites. Here, we describe cryptotephra investigations of two Middle–Upper Paleolithic sites from north‐west Italy, Arma Veirana and Riparo Bombrini. Cryptotephra are present as small ( 75 wt.%) with low FeO ( 2 O/Na 2 O > 1 and P2 is also a high silica rhyolite (>75 wt.%) but with higher FeO (2.33–2.65 wt.%). Shards at Riparo Bombrini (P3) are of the same composition as P1 shards at Arma Veirana, providing a distinct link between deposits at both sites. Geochemical characteristics suggest three possible sources for P1 and P3: eruptions from Lipari Island (56–37.7 ka) in Italy, the Acigöl volcanic field (200–20 ka) in Turkey and the Miocene Kirka‐Phrigian caldera (18 Ma) in Turkey. Eruptions from Lipari Island are the most likely source for P1,3 cryptotephra. This study highlights how cryptotephra can benefit archaeology, by providing a direct link between Arma Veirana and Riparo Bombrini as well as other deposits throughout the Mediterranean.

A Mechanistic Model for Secchi Disk Depth, Driven by Light Scattering Constituents - Steven W. Effler; Christopher Strait; David M. O’Donnell; Adam J.P. Effler; Feng Peng; Anthony R. Prestigiacomo; Susan M. O’Donnell; MaryGail Perkins; Steve C. Chapra (Water, Air, & Soil Pollution, 2017)